RECIPROCAL TEACHING TECHNIQUE ON STUDENTS’ READING COMPREHENSION OF ISLAMIC SENIOR HIGH SCHOOL - Egiyantinah, Siti Habibah; Alek, Alek; Fahriany, Fahriany; Wekke, Ismail Suardi (Institut Agama Islam Negeri Imam Bonjol Padang, 2018)
this article to investigate the empirical evidence about the effect of Survey, Question, Read, Recite and Review and Reciprocal Teaching Technique on Student’s Reading Comprehension for the eleventh grade of SMA Islam PB Soedirman. The research was applied quantitative method and the research design was quasi experimental study. There were two classes used in this research namely Class XI IPA 3 and IPA 4. Class XI IPA 3 was given RTT method as experiment class and Class XI IPA 4 was given SQ3R method as comparison class. Each class consisted of 36 students, so the total number was 72 students. This research was conducted by following procedures: giving pretest, implementing treatment and giving protest. The data was analyzed by two-ways ANOVA. The findings of this research were: (1) there was no effect of teaching methods towards students’ reading comprehension (2) there was interactional effect between teaching method and students’ learning style towards students’ reading comprehension (3) therewere differences of students’ reading comprehension score between students who own visual learning style in RTT and SQ3R class and those who own auditory learning style in class.